The Risk Factors of Pneumonia Disesase at Babies Under Five Years Old Based on Measles Imune Status and Breast Freeding Exclusive Status - Dian Eka Puspitasari; Fariani Syahrul (Jurnal Berkala Epidemiologi, 2015)
Pneumonia in infants is included in the top 10 most illnesses in children aged 1-5 years in the hospitalization of children at the Regional Public Hospital of Bhakti Dharma Husada (RSUD Bhakti Dharma Husada) Surabaya in the period 2011-2013. This study aims to analyze the risk factors for pneumonia in infants based on measles immunization status and the status of exclusive breastfeeding (ASI). The type of research is analytic observational with a case-control design. This research was conducted in the inpatient ward of the RSUD Bhakti Dharma Husada Surabaya in January - April 2014. The study sample consisted of 20 samples of cases of toddlers suffering from pneumonia taken in total populations and 40 control samples of toddlers taken from neighboring cases and had no history of pneumonia or other respiratory diseases. The independent variables studied included measles immunization status and exclusive breastfeeding status, while the dependent variables studied included pneumonia in infants. Data analysis using StatCalc by calculating the odds ratio The results showed that most toddlers with pneumonia were male and aged 1 to less than 2 years. Measles immunization (OR = 10.23; 95% CI = 1.60-107.95) and exclusive breastfeeding (OR = 7.00; 96% CI = 1.82 - 29.49) affect the incidence of pneumonia. The importance of increasing parental awareness about measles immunization and exclusive breastfeeding can prevent the incidence of pneumonia in infants.